2017
DOI: 10.1136/oemed-2016-104172
|View full text |Cite
|
Sign up to set email alerts
|

Occupational lifting and rhegmatogenous retinal detachment: a follow-up study of Swedish conscripts

Abstract: Our study supports the hypothesis that heavy occupational lifting is a risk factor for RRD. Information on myopia degree and socioeconomic status is necessary when studying the association between occupational lifting and RRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 33 publications
(24 reference statements)
1
9
0
Order By: Relevance
“…Inclusion criteria have been surgically treated rhegmatogenous retinal detachment, exclusion criteria were tractional, traumatic or exudative retinal detachment [8]. The highest overall incidence, thus in a limited group of study subjects, could be found in the retrospective study by Farioli et al [22] of a cohort of Swedish men conscripted for compulsory military service born between 1949 and 1951. It showed an incidence of 28 rhegmatogenous retinal detachment cases per 100,000 person-years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Inclusion criteria have been surgically treated rhegmatogenous retinal detachment, exclusion criteria were tractional, traumatic or exudative retinal detachment [8]. The highest overall incidence, thus in a limited group of study subjects, could be found in the retrospective study by Farioli et al [22] of a cohort of Swedish men conscripted for compulsory military service born between 1949 and 1951. It showed an incidence of 28 rhegmatogenous retinal detachment cases per 100,000 person-years.…”
Section: Discussionmentioning
confidence: 99%
“…A certain trend towards higher incidences in the male sex has been demonstrated in various studies [2-8, 10, 12-14, 16-18, 23, 24]. Other risk factors are family predisposition [6, 15, 19, 20], summer months [11] and heavy lifting in everyday working life [4, 22]. As for education and affluence, there are trends towards higher [4] but also lower income and education [12, 22] as potential risk factors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a case report was published in 2014, describing a healthy 27-year-old Turkish construction worker, who suffered from valsalva retinopathy after heavy cement bag lifting [22]. Long ago, it was proved that heavy lifting is accompanied by an increase in the [23]. A population-based study in Denmark also found no association between occupational heavy lifting and RD [24].…”
Section: Discussionmentioning
confidence: 99%